The Influence of Supervision and Motivation on Teacher Performance (Case Study at Smpn 40 Bandung City) - Rahmawati, Irma; Avianti, Widiya; Komar Priatna, Deden (Greenation International Journal of Law and Social Sciences, 2024)
Supervision and motivation are factors that affect a person's performance. Based on observations in the field, the researchers found that there were several indications that were considered less than optimal both in terms of supervision and motivation which were feared to affect teacher performance which could have a bad impact on the organization itself. The low teacher performance is thought to be caused by inappropriate supervision of the principal, apart from supervision problems, it is also suspected to be due to motivational problems. Motivation can also be seen as an integral part of the teaching and learning process that is less than optimal. The purpose of this research is to describe supervision, work motivation and performance of SMPN 40 Bandung City and to examine the influence of supervision and motivation on performance (a study at SMPN 40 Bandung City). The method used is descriptive survey method and explanatory survey. The type of investigation in this study is causality. The unit of analysis is the teachers of SMPN 40 Bandung City with a population of 56 teachers. The time horizon in this study is cross sectional and the analytical methods used are frequency distribution and path analysis The findings of this study are the principal of SMPN 40 Bandung City has appropriate supervision, high motivation of SMPN 40 Bandung City teachers and high performance SMPN 40 Bandung City teachers. Supervision and motivation affect teacher performance. However, when viewed partially, it turns out that motivation is more dominant in influencing performance than supervision, therefore motivation is a priority in improving teacher performance